Penerapan Hibridisasi Algoritme Genetika dan Simulated Annealing untuk Optimasi Vehicle Routing Problem pada Kasus Pengangkutan Sampah Kota Denpasar - Putu Gede Pakusadewa; Candra Dewi; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Handling municipal garbage is one of the problems that exist in a big city including the city of Denpasar. The amount of waste on certain days such as religious holidays will increase significantly where the 4-shift schedule used is inadequate to transport all the waste at certain TPS. Determination of the optimal route of garbage transportation is needed to save work time, lower operational costs and capable to transport all the waste. This research applies hybrid genetic algorithm and simulated annealing to optimize municipal garbage collection transportation route. The representation of chromosomes used is permutation representation with two segments namely the route segment and the truck segment. The process stage uses crossover with order crossover method and mutation with one-cut point method. The test results show the best fitness value is 1,042568623 with optimal parameters using population number = 400, crossover rate and mutation rate = 0.9 and 0.1, number of generations = 200, initial temperature = 1000, final temperature = 1, and alpha/cooling rate = 0.1. The result of this research is recommendation of optimal transportation route to collect garbage from a number of TPS.